Casais em segunda união: desafio e encaminhamentos pastorais - Colen, Alessandro Almeida (2012)
The processes of secularization which the country has undergone have made visible progress in the number of couples who separate and return to live in marital union. This situation does not reduce their willingness and desire to join a community of faith. Thus it causes a climate of pastoral need in order to assist these couples, who are in hard and sometimes very delicate and conflicting conditions. Therefore, every day we see the creation of pastorals that are ready to walk together and provide the Gospel service of solidarity with the couples on a second marriage. In this task, this dissertation attempts to point out some possibilities for therapeutic help, talking to couples therapy in an analytical way and pastoral counseling, referencing also the position of the Roman Catholic Church and its pastoral guidelines.